Explaining math and science achievement of public school children in the Philippines - Quimbo, Stella Luz A. (2003)
This paper presents estimates of an education production function which includes measures of the home learning environment and school inputs recorded at the student level. These are important variables but are often overlooked as a result of data limitations. Results suggest that minimizing teacher absenteeism and effectively providing basic learning materials in schools can improve the math and science achievement of current as well as future generations of students. The home learning environment, including parental education, was found to have a significant effect on student performance.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 72)
Keywords: Education -- Philippines; Academic achievement -- Philippines; Student growth (Academic achievement) -- Philippines